24.4k views
4 votes
Solve the equation for x.

5x - ( 4x - 1) = 2
1
a.
C.
1
9
bi
b. - 1
d.
1

2 Answers

7 votes

Answer:

x = 1

Explanation:

5x - (4x - 1) = 2

Let's get rid of the parenthesis

Multiply whatever is in the parenthesis by -1 since there is a minus sign before it

5x - 4x + 1 = 2

Move common terms to one side, so subtract 1 from both sides

5x - 4x + 1 = 2

- 1 - 1

5x - 4x = 1

Subtract the 5x by 4x

x = 1

User Wdphd
by
4.7k points
3 votes

Answer:

x = 1

Explanation:

5x - (4x - 1) = 2

5x - 4x + 1 = 2 {Distribute property (-1) is distributed with 4x and (-1)}

Combine like terms

x + 1 = 2

Subtract 1 from both sides

x = 2 - 1

x = 1

User Ameer
by
5.2k points